Aggressive behavior and the influencing factors at five schools in Johor Bahru - Yahaya, Azizi (Elixir journal Psychology, 2012)
The objective of the study is to identify the perception of the students on aggressive attitude in five secondary schools in Johor Bahru town. This study also attempts to identify the factor of aggressive and types of aggressive attitude in the school. About 260 questionnaires were distributed at random stage to aggressive student from form one, two and four. The instrument used was the Mooney Problem Check List which was later analysis by the SPSS11.5 (Statistical Package For Sosial Science). It contained 64 likert skill items. The reliability value (alpha croanbach) of the instrument was 0.81. Descriptive statistic in the form of mean, standard deviation and percentage was used in data analysis. As a whole, the result of the study shows the level students aggressiveness in secondary schools in Johor Bahru area were quite high. The hypothesis shows that there is no significant difference between aggressive factor and student rate. There is significant relationship between types of aggressive and family income. Students’ perception between aggressive attitude in secondary school show that environment of school is dominant (mean 4.1), less attention from family background (mean 3.8), students’ attitude (mean 3.88), psychology (mean 3.65) and their friends (mean 3.68). The most aggressiveness among student was shown that physical attitude (mean 3.57), verbal (mean 3.53) and anti social (mean 3.34). Thus this research shows that the aggressive attitude among students in Johor Bahru town is quite high. The study suggested that the school should identify aggressiveness culture among the students and should implement the peer program therefore the problems will be decrease.